Runoff Generation and Soil Erosion at Different Age of Acacia Plantation in Hoa Binh Province, Vietnam - Kolyan, Chin (H. : ĐHQGHN, 2019)
To determine the characteristics of runoff generation and soil erosion at the different ages of Acacia plantation in Luong Son headwater of Vietnam, four plots (15m2 plot-1) were set up. Of those, two plots were at up-hill and down-hill in 1-year-old and two plots in 5-years-old Acacia plantation. Soil erosion and runoff were monitored during rainy season from April to September 2018. The main finding includes: (1) Runoff coefficient at Acacia 1-year-old down and up was ranged from 0.36% - 0.46% with the average 0.41%. Acacia 5-years-old, down and up was 0.35% - 0.39%, averaged 0.37%. It shows the slightly different between the locations of two years due to the different ground cover but not statistical significant different; (2). Soil erosion in Acacia-1 and Acacia-5 year old were 21.84 and 14.20 ton/ha/6months, respectively. The data for soil erosion was statistical significant different between two ages of Acacia plantation. Soil erosion at the study site was very high within strong erosion base on TCVN5299: 2009; (3) Both runoff and soil erosion had strong relationship with precipitation (R2 range from 0.52-0.85, with P-value = 0.00). This result suggests that more concerning and applying suitable management for reducing the negative impact of Acacia plantation at the headwater of Vietnam is necessary